A Rare Tumour of the Breast: Carcinosarcoma - Ilhan, Enver (Elmer Press, 2010)
Carcinosarcoma of the breast, also known as metaplastic carcinoma, is rare with very few cases reported in the literature. A 46-year old female patient presented with a mass in her left breast. Physical examination, ultrasonography and mammography findings were consistent with malignancy. The mass was totally removed. Histopathological examination revealed carcinosarcoma of the breast. Histologic grade of the tumour was III. Ki67 proliferation index was found 40% positive. Tumour cells were positive for p53 (70% positive), c-erb-B2 (5% positive), pancytokeratin and EMA in carcinomatous areas, and vimentin in sarcomatous areas. There was no metastasis in axillary lymph node and distant metastasis. The patient is receiving chemotherapy and is under follow-up in the 54th month. Along with a review of the literature, we present the information regarding the clinical and histological findings and treatment of the patient who was operated due to breast carcinosarcoma. KEYWORDS: Breast; Carcinoma; Carcinosarcoma